Analisis Penerapan Pendekatan Audit Jarak Jauh Dampak dari Pandemi Covid-19 (Studi Kasus : Inspektorat Jenderal Kementerian Kesehatan RI) - Fifit Awaliah; Dwi Setiawan S (Owner : Riset dan Jurnal Akuntansi, 2023)
The Covid-19 pandemic has greatly impacted many aspects, including how the audit works at the Inspectorate General of the Indonesian Ministry of Health. With various kinds of restrictions ranging from travel restrictions and interaction restrictions, it becomes an obstacle for internal audit activities to be carried out directly. Therefore the Inspectorate General needs alternative procedures or ways of conducting audit activities, namely by using a remote audit approach. This study aims to obtain references to develop guidelines for implementing the remote audit approach during a pandemic and under normal conditions while still paying attention to audit quality. In this study analyze the resources owned and alternative ways of conducting audits using a remote audit approach. The research method used is descriptive qualitative with data sources derived from interviews with employees and officials within the Inspectorate. The results of the study show that there are different ways at each stage of the audit that require information technology assistance and the development of data analytics processes in its implementation as well as several things that need to be considered in developing a strategy for implementing the remote audit approach, spesifically the readiness of human resources, adequate information technology, budget available, as well as compensation that can be given to the auditor in terms of carrying out this remote audit.